The development and management of territorial heritage: The recent experience of Argentina - Bustos Cara, Roberto Nicolas (2017)
«Identity, culture, heritage and territory are convergent concepts in the sense that their essential constitutive attributes make up the network of meanings that sustain the world of objects and actions […]. This convergence should be interpreted in two complementary ways, oriented towards both the past and the future, acting as static references, or as the driving force of a dynamic that assumes the form of an interested transfer or an ever-renewing creation» (Bustos Cara, 2004: 17). As Guy Di Meo said, heritage values are defined like the territory, as «time which makes sense and has meaning as if it were history crystallised into an object, place or event. It has two natures, the material and the ideal. It has a mnemonic function. They insert the social fabric into a historical continuity made up of solid cultural references that generate ideological and political control». «How can we understand territory without assigning a heritage value to it?». «Neither territory nor heritage represent an a priori fact. Yet every object may have a heritage function and every space may be transformed into a territory, if one or the other is integrated in a communicational context» (Di Meo, 1998: 59). The idea of heritage covers a broad and extremely dynamic conceptual field, and this is why it is difficult to establish an institutional management structure that can moderate between conflicts and may keep its dynamic character in check. In this sense, there is a close relation between heritage and territory and between heritage and development, and this relation is always variable in content, depending on the ideological, political, economic or cultural context from which it is analysed. In times of the construction or reconstruction of nation states, or at times when there is a dominantly liberal or neoliberal vision within the globalisation framework, then the processes that lead to heritage status and its institutionalisation have acquired different characteristics and scales.